2019
DOI: 10.1021/acs.orglett.9b01999
|View full text |Cite
|
Sign up to set email alerts
|

Iron(0)-Mediated Reformatsky Reaction for the Synthesis of β-Hydroxyl Carbonyl Compounds

Abstract: An efficient, economical, and practical Reformatsky reaction of α-halo carbonyl compounds with aldehydes/ketones by using cheap and commercial iron(0) powder as reaction mediator is developed. The reactions proceeded effectively in the presence of a catalytic amount of iodine (20 mol %) to afford the synthetically useful β-hydroxyl carbonyl compounds in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…Based on the above results and studies reported in the previous reference, a tentative mechanism for the Cu-Catalyzed, Mn-mediated propargylation and allenylation of aldehydes with propargyl bromides was proposed in Fig. 3 [ 52 – 56 ]. Mn, which is severed as a strong reducing agent, reduced the Cu I to Cu 0 in an active form in situ.…”
Section: Introductionmentioning
confidence: 80%
“…Based on the above results and studies reported in the previous reference, a tentative mechanism for the Cu-Catalyzed, Mn-mediated propargylation and allenylation of aldehydes with propargyl bromides was proposed in Fig. 3 [ 52 – 56 ]. Mn, which is severed as a strong reducing agent, reduced the Cu I to Cu 0 in an active form in situ.…”
Section: Introductionmentioning
confidence: 80%
“…In addition, in contrast to most of the aforementioned relatively expensive metallic catalysts (usually stoichiometric amounts), iron(III) salts, which have been proven to be robust Lewis acids for catalyzing a wide range of organic transformations, [11,12] are more attractive because they are cheaper and less toxic. In continuation of our interest in iron chemistry [13] and in developing efficient methods for the synthesis of fluorine-containing organic molecules, [14] herein we report an efficient iron(III)-catalyzed difluoroalkylation of aryl alkyne with difluoroenol silyl ether in the presence of trimethylsilyl chloride [15] in dichloroethane (DCE), leading to the corresponding products of αalkenyl-α,α-difluoroketones in moderate to good yields (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction, the Reformatsky reaction has emerged as one of the most widespread strategies for the formation of new carbon–carbon bonds . To date, various methods based on metal-mediated Reformatsky reactions of α-halo carbonyl compounds with aldehydes or ketones have been widely developed. Among the reported methods, homogeneous enantioselective Reformatsky-type reactions based on the use of Me 2 Zn have been successfully employed to generate chiral β-hydroxy esters . A breakthrough in the development of Me 2 Zn-mediated catalytic enantioselective Reformatsky reactions with aldehydes or ketones as electrophiles has been made by Cozzi and coauthors.…”
Section: Introductionmentioning
confidence: 99%